PERBANDINGAN POSISI KNEE JOINT FLEKSI DAN EXTENSI PEMERIKSAAN LUMBOSACRAL ANTERO POSTERIOR (AP) SUPINE DALAM MEMPERLIHATKAN DISCUS INTERVERTEBRALIS - Noerma Kurniawa, Ceccare; Cahyati, Yeni; Agung Basuki, Rizki (Perhimpunan Radiografer Indonesia (PARI), 2020)
Background : Supine examination of lumbosacral antero posterior projection (AP) is used to obtain a clear lumbosacral radiograph, one of which shows an intervertebral disc. The objective the research was to determine the knee joint flexion position and knee joint extension position on the antero posterior lumbosacral (AP) Supine examination in the appearance of intervertebral discs. Methods : Research of the position of the knee joint flexion and extension on the lumbosacral antero posterior (AP) Supine examination in displaying intervertebral discs, this is a comparative descriptive study, the researchers compared the position of the knee joint flexion and extension on Supine's lumbosacral antero posterior (AP) examination in showing the intervertebral disc so that it can be seen which position is better in performing Supine antero posterior (AP) lumbosacral radiographic examination in showing the intervertebral disc and which radiograph results. the best in establishing the diagnosis Result : From the research data in showing the knee joint flexion and extension position, the mean value of the joint gap on Supine's lumbosacral (AP) examination in showing L-1 intervertebral disc in the knee joint flexion position was 8.8 mm while the knee joint extension position was 8.8 mm. 7 mm intervertebral disc L-2, knee joint flexion is 10.2 mm, while knee joint extension is 9.2 mm, intervertebral disc L-3, knee joint flexion is 9 mm, while knee joint extension is 7.8 mm , intervertebral disc L-4 knee joint flexion position is 11 mm while knee joint extension is 9.8 mm, lumbal sacrum joint knee joint flexion is 9 mm while knee joint extension is 6.6 mm. Conclusion : The position of the knee joint flexion on the lumbosacral antero posterior (AP) examination Supine is better at showing the anatomical structure of the vertebral bodies, intervertebral discs, intervertebral foramen L1-L4, spinous processes, sacrum, and intervertebral disc joint gaps, intervertebral disc. The position of the knee joint extension on the examination of the lumbosacral antero posterior (AP) Supine can reveal the anatomical structures of the vertebral bodies, intervertebral discs, intervertebral foramen L1-L4, spinous processes, sacrum, but in revealing intervertebral disc joints, Intervertebral disc.